Vasectomy reversal: a review on outcomes using a loupe-assisted vasovasostomy approach. (4th December 2020) - Ravindraanandan, Manoj; Ong, Chea Tze; Elhadi, Mohammed; Mahmalji, Wasim; Akhtar, Mehmood
Abstract: Introduction: Vasectomy is a popular choice of contraception worldwide. In the UK, vasectomy reversal is not usually licensed under the NHS with reports on outcomes being limited. Microsurgical reversal is a technique commonly performed under the operating microscope. Loupe magnification, however, is emerging as a safe and reliable technique to perform microsurgery. Method: Loupe-assisted microsurgical vasovasotomies were performed on 14 men in a 3-year period. Indications for the procedure were for fertility only. Semen analysis variables were measured against European Association of Urologists (EAU) guidelines at six weeks. Patients were followed-up at clinic in three months. Data were collated using operation notes and cytology results, and analysed using descriptive statistics. Pearson's correlation coefficient was used to compare years after vasectomy, and age to sperm count. Results: The average sperm count in our group was 41.3 million per millilitre (median 29.95, range 2.7–107.8) at 6 weeks. Seventy-five per cent were found to have positive sperm motility, and all had acceptable sperm morphology at follow-up. A very low to weak correlation between time after vasectomy and age, with sperm count. Conclusion: We have demonstrated that fertility and post-operative outcomes using a loupe-assisted microsurgical vasovasotomy approach are favourable as per EAU guidelines.